RITUALS IN NEW RELIGIOUS MOVEMENTS IN INDIA - Chandrankunnel, Mathew (Journal of Dharma, 2006)
Rituals are part of every society, civilization and religion. Recently, archaeologists discovered the statue of a man devoutly offering flowers to the statue of a snake which is estimated to be 70,000 years old. According to the archaeologists, these statues might be the earliest expressions of ritualism. Thus, the symbolic expression or rituals are very ancient, perhaps even dating back to the evolution of the homosapiens. Thus, rituals and symbolic performances became part and parcel of every human society from its genesis, giving meaning to life and strengthening individual and social bonding. The famous French philosopher Paul Ricour and Mircea Eliade theorised in the twentieth century about the importance and the existential need of rituals in religions and human societies. Connecting rituals with the myths they interpreted that ritual enactments are the desire of the participants to go back to the period of Ithihasa or Ilud Tempore, to the primordial time and space, in their attempt to recharge themselves by keeping in touch with their origins. As humanity evolved through millennia, social and religious rituals were established defining and expressing social and religious identity and differentiation symbolically.